Analisis Hukum Pelaksanaan Akad Salam Dalam Transaksi Komoditas Syari’ah - mu’alimatul, arum; Abdillah, Muhammad Hanif (IKRAITH-EKONOMIKA, 2025)
The purpose of this paper is to provide an understanding of what is referred to as a salam contract and how its legal status is determined based on Islamic law. As the economy becomes more efficient today, the salam contract can serve as an alternative that facilitates and benefits both parties involved in an economic transaction, particularly in buying and selling activities. This study employs a qualitative approach through an article study. The collected data consists of analyses from various sources, including scholarly articles and journals. One type of financial transaction that aligns with the principles of Sharia, such as the principles of justice and the prohibition of riba (usury), is the salam contract. By understanding the pillars, provisions, and conditions of the salam contract, society can conduct financial transactions more effectively and in accordance with Islamic law. The primary purpose of a salam contract is to enable producers to obtain the necessary upfront funds for the production process. According to Islamic law, engaging in a salam contract is permissible, supported by legal foundations derived from the Qur’an, Hadith, and the consensus (ijma’) of scholars. Moreover, there are several principles, provisions, and conditions required tensure that the salam contract is carried out legitimately according to Islamic law. In daily life, the practice of the salam contract can be observed, especially when goods are sold within the community. In such transactions, the salam contract functions as a means to ensure that the transaction is valid and compliant with Islamic law.